Announcement - The Paper Award of Tribology Online - - Masabumi Masuko (Japanese Society of Tribologists, 2012)
The Japanese Society of Tribologists is pleased to announce that the 2011 Paper Award of Tribology Online was awarded to:“Analyses of the Adsorption Structures of Friction Modifiers by Means of Quantitative Structure-Property Relationship Method and Sum Frequency Generation Spectroscopy,” by Hiroaki Koshima, Hideki Kamano, Yoshio Hisaeda, Huijin Liu, Shen Ye, Vol. 5, No. 3 (2010) 165-172.and“The Effects of Hydrogen on Microstructural Change and Surface Originated Flaking in Rolling Contact Fatigue," by Hideyuki Uyama, Hiroki Yamada, Hideyuki Hidaka, Nobuaki Mitamura, Vol. 6, No. 2 (2011) 123-132.The Award Medals were presented to the authors by Dr. Yoshio Kumada, the former President of the Japanese Society of Tribologists, at the JAST Annual Meeting on 15th May, 2012.The Paper Award of Tribology Online is given annually to the author(s), either the JAST members or non-members, of the paper(s) judged as the best paper(s) published in Tribology Online (TROL) for the previous three years. All papers that appeared in TROL for the three years are reviewed by the JAST Awards Committee.